1998
DOI: 10.1038/32925
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of wild-type p53 by hypoxia-inducible factor 1α

Abstract: Although hypoxia (lack of oxygen in body tissues) is perhaps the most physiological inducer of the wild-type p53 gene, the mechanism of this induction is unknown. Cells may detect low oxygen levels through a haem-containing sensor protein. The hypoxic state can be mimicked by using cobalt chloride and the iron chelator desferrioxamine: like hypoxia, cobalt chloride and desferrioxamine activate hypoxia-inducible factor 1alpha (HIF-1alpha), which stimulates the transcription of several genes that are associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
492
5
9

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 787 publications
(526 citation statements)
references
References 20 publications
20
492
5
9
Order By: Relevance
“…CK2 is also known to phosphorylate p53, enhancing its stability and its activity. 60 In severe hypoxia or in anoxia, HIF-1a has been described to increase p53 stability 61 through an inhibition of its degradation by Mdm2. 62 This interaction between HIF-1a and p53 leads to an inhibition of HIF-1 activity because HIF-1a is targeted for degradation by Mdm2.…”
Section: Discussionmentioning
confidence: 99%
“…CK2 is also known to phosphorylate p53, enhancing its stability and its activity. 60 In severe hypoxia or in anoxia, HIF-1a has been described to increase p53 stability 61 through an inhibition of its degradation by Mdm2. 62 This interaction between HIF-1a and p53 leads to an inhibition of HIF-1 activity because HIF-1a is targeted for degradation by Mdm2.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Evans et al 107 demonstrated that knockdown of pVHL resulted in E-cadherin suppression via HIF-dependent induction of E2 box-dependent transcriptional repressors Snail and SIP1, and Krishnamachary et al 108 reported that HIF-1 activation in VHL-deficient cells downregulated Ecadherin, led to the loss of cell-cell adhesion and promoted epithelial to mesenchymal transition through the induction of transcriptional repressors TCF3, ZFHX1A and ZFHX1B/SIP1. Therefore, cellular changes, such as loss of intercellular junctions and epithelial de-differentiation involving HIFdependent as well as HIF-independent molecular pathways 48,[106][107][108] in addition to HIF-dependent and -independent alterations in p53 or NF-kB activity, 34,35,49,51 HGF signaling, 45,50,109 and modifications in ECM turnover and re-modeling [42][43][44][45][46][47] create the molecular environment for the development CC-RCC, which most likely requires additional genetic events. The importance of HIF activation in CC-RCC pathogenesis and growth is furthermore underscored by experimental and clinical studies, which demonstrated that inhibition of HIF-a translation by pharmacological targeting of mTOR correlated with reduced tumor growth, 110 and that increased expression of certain HIF target genes, such as CXCR4, as well as E-cadherin suppression was associated with disease progression.…”
Section: Pvhl and Renal Cell Cancermentioning
confidence: 99%
“…These include, among others, tumor suppressor protein p53 and the c-Myc proto-oncogene. [34][35][36] A more recent example is the ability of HIF-1a to associate with the intracellular domain of Notch (Notch ICD), thereby increasing the expression of Notch-target genes, such as Hey and Hes. 37 This and other HIF-a/non-PAS domain protein interactions have to be considered when interpreting experimental phenotypes that result from VHL gene deletion in the laboratory mouse.…”
mentioning
confidence: 99%
“…Expression of VEGF is required to stimulate angiogenesis and solid tumor vascularization, a critical step in tumor progression and also in hematologic malignancies (Semenza, 2000;Maxwell et al, 2001). Intrinsically, hypoxic conditions in solid tumors are supposed to allow selection for P53 mutations (Graeber et al, 1996;An et al, 1998).…”
Section: Introductionmentioning
confidence: 99%